Shadow economy in the context of threats to the economic security of the state - M. M. Begichev; A. V. Vlasov; K. I. Avtomonova (Путеводитель предпринимателя)
The article is devoted to the study of the essence and various consequences of the shadow economy. The most significant feature of the shadow economy is the fact that it has a significant negative impact on the economy of the region, country and/or economic unions. It is worth noting the fact that quite successful work has been carried out to combat the shadow economy for quite a long time, all the same, the threats emanating from it remain quite high. Based on the results of the study, the authors come to the conclusion that it is necessary to further improve the work of state bodies and business structures aimed at working together to counter the shadow economy.